Cadena de valor en la generación del conocimiento para la gestión de la biodiversidad (2016)
We began our study with an overview of the relationship between knowledge and decisions, especially the so-called science – policy gap. We develop the argument that the lack of explicit distinction among decision makers, among data, information, and verified knowledge, very often contributes to deepen the mentioned gap. Therefore, we propose a conceptual framework for the functional integration of data, information, and knowledge, to be applied in biodiversity research, differentiating the scientific instances of consignation, integration, and interpretation of events. When applied to the research endeavors of the Humboldt Institute, the differentiation of these components may help create a valuechain of pertinent knowledge in real world situations regarding biodiversity and ecosystem services management in the territory.